How do you find the solution of the system of equations 5x + 4y = 6 and -2x - 3y = -1?

1 Answer
Jun 20, 2018

Through elimination, we get:
x=2
y=-1

Explanation:

Manipulate the equations so that you can eliminate one of the variables. One possibility is to multiply the first equation by 2, and multiply the second equation by 5:

+10x+8y=12
-10x-15y=-5

Then add the two equations together to eliminate x and solve for y:
0-7y=7
y=-1

Now substitute the value of y into either of the original equations to find x:
5x+4y=6
5x+4(-1)=6
5x = 6+4=10
x=2